Ghana’s agrifood system structure and drivers of transformation - Diao, Xinshen; Ellis, Mia; Pauw, Karl; Randriamamonjy, Josee; Thurlow, James (International Food Policy Research Institute, 2023)
Ghana experienced rapid economic growth with an annual GDP growth rate of 6.6 percent between 2009 and 2019 (GSS 2023). Restrictive COVID-19 policy measures in 2020 caused a slowdown in growth (Amewu et al. 2020), with the rate falling to just 0.5 percent in that year (World Bank 2023a). Economic growth rebounded to 5.4 percent in 2021, but this growth was fueled by excessive government borrowing to finance an ambitious public infrastructure campaign and ushered in a severe financial crisis in Ghana. By 2022, the fiscal deficit had reached almost 10 percent of GDP and the total debt-to-GDP ratio had skyrocketed to 90 percent, resulting in rampant inflation (32 percent year-on year), a doubling of interest rates (from 14 to 28 percent), and a sharp currency depreciation (40 percent) (World Bank 2023b; Naadi 2023). Economic growth slowed to 3.2 percent in 2022 and is projected to decline further to 1.6 percent in 2023 (World Bank 2023a). Although President Akuffo-Addo blamed “malevolent forces” (Financial Times 2023)—including the global commodity market shock caused by Russia’s invasion of Ukraine, which by some accounts had only a minimal effect on Ghana’s economy (Arndt et al. 2023; Diao and Thurlow 2023)—the economic situation eventually forced the government to agree to an IMF bailout of US$3 billion in 2023. This will be in force for three years.